肾癌外泌体标志物组及其应用 (2019)
本发明涉及肾癌外泌体标志物组及其应用，所述标志物组包括：外泌体源性VHL基因的mRNA、外泌体源性PBRM1基因的mRNA、外泌体源性ATM基因的mRNA、外泌体源性PTEN基因的mRNA和外泌体源性SETD2基因的mRNA。本发明所述标志物组通过检测外泌体源性VHL基因、PBRM1基因、ATM基因、PTEN基因和SETD2基因的mRNA的检测和相应的诊断模型，可实现肾癌患者与非肾癌患者的区分，尤其是早期肾癌样本（例如临床T1肾癌）与非肾癌样本（例如正常人以及单纯性肾囊肿、错构瘤等肾脏良性占位病变）的区分，解决临床上早期肾癌难以及时、准确诊断的缺陷。 The invention relates to a renal cancer exosome marker group and application thereof. The marker group comprises mRNA of an exosome-derived VHL gene, mRNA of an exosome-derived PBRM1 gene, mRNA of anexosome-derived ATM gene, mRNA of an exosome-derived PTEN gene and mRNA of an exosome-derived SETD2 gene. By means of detection of the mRNAs of the exosome-derived VHL, PBRM1, ATM, PTEN and SETD2 genes and a corresponding diagnosis model, the distinction between renal cancer patients and non-renal cancer patients can be achieved, especially the distinction between early renal cancer samples (suchas clinical T1 renal cancer) and non-renal cancer samples (for example, normal people, simple renal cysts, hamartomas and other benign renal space